2015
DOI: 10.1016/j.ultsonch.2014.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining lignin nanoparticles by sonication

Abstract: a b s t r a c tLignin, the main natural aromatic polymer was always aroused researchers interest. Currently around 90% of this biomaterial is burned for energy. It has a very complex and complicated structure which depends on the separation method and plant species, what determine difficulties to use as a raw material widely. This research presents a physical method to modify lignin by ultrasonic irradiation in order to obtain nanoparticles. The nanoparticles synthesized were dimensionally and morphologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(163 citation statements)
references
References 30 publications
9
153
0
1
Order By: Relevance
“…However, a dramatic increase of aliphatic OH groups ( Figure 5 ) was observed, from 1.91 mmol g -1 (not sonicated) to 5.45 mmol g -1 (sonicated for 1 h; see Figure 4b), and this is an indication of splitting of ether or ester bonds releasing OH groups. Gilca et al (2015) reported similar results. More over, peak sharpening for several groups is indicative of depolymerization.…”
Section: Influence Of Sample Preparation On Lssupporting
confidence: 63%
“…However, a dramatic increase of aliphatic OH groups ( Figure 5 ) was observed, from 1.91 mmol g -1 (not sonicated) to 5.45 mmol g -1 (sonicated for 1 h; see Figure 4b), and this is an indication of splitting of ether or ester bonds releasing OH groups. Gilca et al (2015) reported similar results. More over, peak sharpening for several groups is indicative of depolymerization.…”
Section: Influence Of Sample Preparation On Lssupporting
confidence: 63%
“…The nanolignin dispersions were very stable in pure water because no specific aggregation occurred within 60 days, which was explained by the relatively high negative ζ-potential of about −60 mV in pure water at pH values from around 5 to 11. This work yielded more spherical nanoparticles compared to other methods [16,35,36], which represents an important advantage for advanced applications. Particles could be dried and dispersed using sonication.…”
Section: Production Of Nano-/microsized Lignin Materialsmentioning
confidence: 94%
“…Gilca et al [36] used sonication for the size reduction of wheat straw and Sarkanda grass lignin. In contrast to the sonication carried out by Tortora et al [20], which caused crosslinking and an increase in molecular weight, this sonication process resulted in decreasing molecular weight and is roughly considered as mechanical treatment.…”
Section: Production Of Nano-/microsized Lignin Materialsmentioning
confidence: 99%
“…To achieve a good mixing and to reduce the particles size of the composite material, vortex homogenization was used, followed by ultrasonic treatment (20 kHz). 59 Phase separation was never observed, even after ultracentrifugation.…”
Section: Resultsmentioning
confidence: 99%